A Rare Case Report of a Consecutive Rib Fractures as an Isolated Obstetrical Complication - DjakoviÄ‡, Ivka; Potkonjak, Ana Meyra; Murn, Filip; ZubÄiÄ‡, Vedrana; KoÅ¡ec, Vesna (Open Access Macedonian Journal of Medical Sciences, 2020)
AIM: The aim of the following paper is to present the case of a term neonate with consecutive posterior rib fractures as an isolated finding after birth. METHODS: In the medical literature, there have been reported some sporadic cases indicating rib fractures in neonates. We present literature review and report a rare case of consecutive posterior rib fractures in neonate born following an uneventful pregnancy and uncomplicated labor. MAIN FINDING: The most common factors that can lead to rib fractures are birth trauma, cardiopulmonary resuscitation, and underlying disorders influencing bone development. In the presented case, there were no signs of other bone fractures or systems involved. CONCLUSION: Isolated form of consecutive posterior rib fracture after birth is a rare obstetrical complication. It is most likely caused by birth trauma but should be interpreted as a clinical sign of the potential syndrome. A decision whether to perform an X-ray depends on a physical examination of the newborn within the 1st h of life.